Answer:
k = -11
Explanation:
Let
![p(x) = x^3-6x^2+kx+10](https://img.qammunity.org/2021/formulas/mathematics/high-school/ygd42w3lqgo6fyhh17ghjvvue2bzf51va0.png)
And x+2 is a factor of p(x)
Let x+2 = 0 => x = -2
Putting in p(x)
=> p(-2) =
![(-2)^3-6(-2)^2+k(-2)+10](https://img.qammunity.org/2021/formulas/mathematics/high-school/gzpwluetqivrquce64nt6eew2djwqn97qr.png)
By remainder theorem, Remainder will be zero
=> 0 = -8-6(4)-2k+10
=> 0 = -8-24+10-2k
=> 0 = -22-2k
=> -2k = 22
Dividing both sides by -2
=> k = -11